Nonlinear Plasmonic Metasurfaces. Issue 18 (15th July 2018) - Rahimi, Esmaeil; Gordon, Reuven
Abstract: The nonlinear optical response of materials allows optical functionality not seen in linear devices, such as switching, wavelength conversion, and adaptive optics. Unfortunately, the nonlinear optical response is weak in naturally occurring materials, making many ultrafast information processing applications impractical from an efficiency point of view. Nonlinear plasmonic metasurfaces, as a subset of metamaterials, aim to provide a more efficient and functional nonlinear optical response by tailoring the configuration of nanostructures. Metasurfaces are compact, cascadable, and easy to fabricate with established planar technologies, and therefore deserve particular attention. In this review, advances in nonlinear plasmonic metasurfaces are presented, including theoretical approaches, design methodologies, and key demonstrations of functionality. The theoretical approach first considers the linear response of the plasmonic metal and then uses this to calculate the nonlinear scattering. Design methodologies are considered including limits on gap size enhancements, tunneling and charging effects, and thermal management. Key demonstrations such as efficiency in wavelength conversion, functional wavelength conversion, and switching are also reviewed. Finally, an outlook on the future development in this field of research is offered, aiming at efficient and ultrafast optical information processing. Abstract : Nonlinear plasmonic metasurfaces provide optical functionality in wavelength conversion, beam manipulation, and optical switching. This work reviews the theory of nonlinear plasmonic metasurfaces, design considerations for optimal performance, and key experimental demonstrations of enhanced functionality.